The new territories of tourism in Egypt: a local-global frontier? - Leïla Vignal (Cybergeo)
The transformation of Egypt as a destination for mass tourism has profoundly reshaped the national territory. This article examines how the revolution of Egyptian tourism has led to the development of previously desert areas – the shores of the Red Sea and of the Mediterranean Sea – in an inversion of the previously Nile Valley-centred tourism maps. It shows that those new tourism territories are produced by a combination of processes acting on different geographical scales, from the local to the global. The article examines in particular the combined role of four players: the tourist, the state, the local entrepreneur, and the global tourism industry.